2011
DOI: 10.1586/eop.11.60
|View full text |Cite
|
Sign up to set email alerts
|

Foveal hypoplasia: the case for arrested development

Abstract: The fovea is an anatomical specialization of the vertebrate retina critical for high spatial visual acuity and refined color vision. In mammals, the fovea is present only in humans and primates. It is characterized as a cone photoreceptor-rich region, with a central rod-free avascular zone containing elongated cone photoreceptors and Müller cell processes. A clearer understanding of the molecular mechanisms implicated in foveal development and the consequences of abnormalities of this process is emerging. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…In line with this a recent study of infants with ROP has shown that grading using a measure of MDA has a predictive value for VA and mfERG responses [19]. The probability that abnormal inner foveal structure may have functional consequences raises the question whether there is a time window of opportunity for intervention and remodelling of foveal architecture following an early diagnosis of immaturity after preterm birth [43].…”
Section: Discussionmentioning
confidence: 87%
“…In line with this a recent study of infants with ROP has shown that grading using a measure of MDA has a predictive value for VA and mfERG responses [19]. The probability that abnormal inner foveal structure may have functional consequences raises the question whether there is a time window of opportunity for intervention and remodelling of foveal architecture following an early diagnosis of immaturity after preterm birth [43].…”
Section: Discussionmentioning
confidence: 87%
“…These observations suggest that OS lengthening and foveal pit excavation are 2 distinct events. This is supported by the known timeline of foveal development 21,22 : Foveal pit excavation begins at 28 weeks gestation and is complete by birth, whereas outer segments of cone photoreceptors start to form at 36 weeks but do not reach their full length until approximately 3-4 years of age. The mechanism by which PAX6 regulates various phases of foveal pit formation remains to be determined, but multiple target genes are likely involved in the different phases.…”
Section: Discussionmentioning
confidence: 88%
“…21 Foveal hypoplasia describes a foveal pit or depression that is partially or completely absent. 22 Despite the implications of foveal hypoplasia on vision impairment, the process by which arrested development of the fovea occurs remains unknown. Spectral domain optical coherence tomography (SD-OCT) has improved evaluation of foveal hypoplasia.…”
mentioning
confidence: 99%
“…It should be noted that the eye continues to develop in humans after birth. In particular, the fovea is not fully formed until about 4 to 5 years of age, 26 , 27 and foveal hypoplasia (an underdeveloped fovea) is present in up to 50%–70% of aniridia cases. Therefore, it is possible that START therapy early in life may be able to stimulate foveal development.…”
Section: Discussionmentioning
confidence: 99%